LIKELIHOOD RATING OF FRAUD RISK IN GOVERNMENT PROCUREMENT - Kamal, Mustofa; Tohom, Andilo (The International Journal of Business Review (The Jobs Review), 2019)
Indonesian government procurement regulations have undergone some changes towards improvements in procurement governance from 2003 to 2018. However, the facts of 177 corruption cases in procurement [1] showed an increasing trend from 2004 to 2017. This study aimed to prove the likelihood level of risk of fraud government procurement and exemplify a list of government procurement fraud risk ratings. Qualitative research method is used with survey technique via google form to 52 respondents consisting of procurement group, auditor and procurement trainer or risk management trainer. Prospectively, respondents rated likelihood on 66 risk of procurement fraud. The results showed that there are 5 risks have a "frequent" likelihood, there are 54 risks have "occasionally" likelihood, and 7 risks have "almost never" likehood. These results have implications for government agencies to develop proper response or management of procurement fraud risk in accordance with their likelihood.